PROSES BERPIKIR KREATIF SISWA SMP DALAM MENYELESAIKAN SOAL BILANGAN PECAHAN BERDASARKAN TEORI WALLAS - Agni Melyana; Cecep Anwar Hadi Firdos Santosa; Etika Khaerunnisa (IKIP Siliwangi, 2022)
This study aims to describe the creative thinking process of junior high school students who had high, medium and low capability in solving fraction problems based on Wallas theory. The type of this research is descriptive qualitative. The subjects of this research were students of class VII SMP Negeri 18 Serang City which were selected as many as 3 students to represent each category of creative thinking ability. The instruments used in this study were written test questions and interview guidelines. The data analysis technique was carried out in three stages, namely data reduction, data presentation and verification or conclusion drawing. The results showed that students with high ability for the fluency and novelty indicators had been fulfilled until the verification stage, while for the flexibility indicator it is only at the incubation stage. Students with medium ability for the fluency indicator are fulfilled until the verification stage, while for the flexibility indicator it is only at the preparation stage and for the novelty indicator it is fulfilled until the illumination stage. Student with low ability for indicators of fluency and flexibility are only up to the preparation stage while for the novelty indicator does not fulfilled any stage.